2009
DOI: 10.1007/s10827-009-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

Models of cortical networks with long-range patchy projections

Abstract: The cortex exhibits an intricate vertical and horizontal architecture, the latter often featuring spatially clustered projection patterns, so-called patches. Many network studies of cortical dynamics ignore such spatial structures and assume purely random wiring. Here, we focus on non-random network structures provided by long-range horizontal (patchy) connections that remain inside the gray matter. We investigate how the spatial arrangement of patchy projections influences global network topology and predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…As is evident from the small number of studies thus far concerned with the physiological properties of horizontal connections, the interest in this large fraction of intra-cortical projections is just beginning. In recent modeling studies, it has been demonstrated that the implementation of horizontal connections can dramatically reduce wiring costs (Voges et al, 2010a) and has a strong impact on network dynamics (Kriener et al, 2009). These studies, however, focused on a related class of connections, the so-called long-range patchy connections (for a review see Voges et al, 2010b), which recently received more attention compared to non-patchy, long-distance horizontal connections.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…As is evident from the small number of studies thus far concerned with the physiological properties of horizontal connections, the interest in this large fraction of intra-cortical projections is just beginning. In recent modeling studies, it has been demonstrated that the implementation of horizontal connections can dramatically reduce wiring costs (Voges et al, 2010a) and has a strong impact on network dynamics (Kriener et al, 2009). These studies, however, focused on a related class of connections, the so-called long-range patchy connections (for a review see Voges et al, 2010b), which recently received more attention compared to non-patchy, long-distance horizontal connections.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Voges et al (2010) had a different take on the properties of patchy networks. They asked what effect long distance connections, with various configurations, had on the signal transmission and graph statistical properties of a network.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the rewired ring lattice is unlikely to exactly resemble real neocortical structure, there is strong experimental evidence for clustering among excitatory neurons, as discussed by [27], and predictions of clustering based on spatial considerations have arisen from theoretical work [74].…”
Section: Discussionmentioning
confidence: 99%